Photonic Nanomaterials: Merging Top‐Down and Bottom‐Up Approaches to Fabricate Artificial Photonic Nanomaterials with a Deterministic Electric and Magnetic Response (Adv. Funct. Mater. 3/2020). (17th January 2020) - Dietrich, Kay; Zilk, Matthias; Steglich, Martin; Siefke, Thomas; Hübner, Uwe; Pertsch, Thomas; Rockstuhl, Carsten; Tünnermann, Andreas; Kley, Ernst‐Bernhard
Abstract : In article number 1905722, Kay Dietrich, Thomas Siefke, and co‐workers investigate the transformation of a subwavelength nanostructured metasurface with electric and magnetic responses to a photonic bulk material from morphological and optical perspectives. Departing from a periodic structure, a randomized orientation and arrangement of the metaatoms is forced that preserves their magnetic and electric response. This material combines the advantages of materials fabricated with both top‐down and bottom‐up techniques.